Genetic Variations and Haplotype Diversity of the UGT1 Gene Cluster in the Chinese Population - Yang, Jing; Cai, Lei; Huang, Haiyan; Liu, Bingya; Wu, Qiang (PLOS ONE, 2012)
Vertebrates require tremendous molecular diversity to defend against numerous small hydrophobic chemicals. UDP-glucuronosyltransferases (UGTs) are a large family of detoxification enzymes that glucuronidate xenobiotics and endobiotics, facilitating their excretion from the body. The UGT1 gene cluster contains a tandem array of variable first exons, each preceded by a specific promoter, and a common set of downstream constant exons, similar to the genomic organization of the protocadherin (Pcdh), immunoglobulin, and T-cell receptor gene clusters. To assist pharmacogenomics studies in Chinese, we sequenced nine first exons, promoter and intronic regions, and five common exons of the UGT1 gene cluster in a population sample of 253 unrelated Chinese individuals. We identified 101 polymorphisms and found 15 novel SNPs. We then computed allele frequencies for each polymorphism and reconstructed their linkage disequilibrium (LD) map. The UGT1 cluster can be divided into five linkage blocks: Block 9 (UGT1A9), Block 9/7/6 (UGT1A9, UGT1A7, and UGT1A6), Block 5 (UGT1A5), Block 4/3 (UGT1A4 and UGT1A3), and Block 3′ UTR. Furthermore, we inferred haplotypes and selected their tagSNPs. Finally, comparing our data with those of three other populations of the HapMap project revealed ethnic specificity of the UGT1 genetic diversity in Chinese. These findings have important implications for future molecular genetic studies of the UGT1 gene cluster as well as for personalized medical therapies in Chinese.